Endocrinopathic laminitis in horses with metabolic syndrome: clinical characteristics, treatment and evolution in three patients - case report - Paula, L. A. O.; Lera, K. R. J. L. [UNESP]; Schuh, B. R. F.; Silva, F. F. A.; Nascimento, E. Michelon do; Pagliosa, G. M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
Endocrinopathic laminitis refers to cases of laminitis whose etiology is associated with an endocrinopathy. Horses with Equine Metabolic Syndrome (EMS) have regional adiposity and obesity. There is a positive correlation between obesity and insulin resistance. This report describes three cases of endocrinopathic laminitis in horses with EMS. Patients had body condition score (BCS) ranging from 8 to 9 (scale from 1 to 9), sensitivity to the hoof clamping test and claudication grade 3 or 4 (scale from 1 to 4). There was no history of recent colic, trauma or over exercise. Treatment included non-steroidal anti-inflammatory medication, stall rest, energy restriction for weight loss, hoofing and hoof bandage as needed by each patient. Dietary restriction helped in the treatment of EMS and reduced BCS. Drug treatment, hoofing and hoof bandage decreased the degree of lameness. It is concluded that non-steroidal anti-inflammatory treatment, energy restriction, stall rest, hoofing and hoof bandage are effective in the treatment of endocrinopathic laminitis in horses with equine metabolic syndrome.
Keywords: regional adiposity; horses; lameness; obesity